2018
DOI: 10.1371/journal.pone.0192548
|View full text |Cite
|
Sign up to set email alerts
|

Vehicle development, pharmacokinetics and toxicity of the anti-invasive agent 4-fluoro-3’,4’,5’-trimethoxychalcone in rodents

Abstract: Effective inhibitors of invasion and metastasis represent a serious unmet clinical need. We have recently identified 4-fluoro-3’,4’,5’-trimethoxychalcone or C16 as a potent anti-invasive molecule. In this paper, we report on the development of an optimized vehicle for oral administration of C16. We also explore its pharmacokinetic and toxicity profile in rodents as a prelude to a broad-scope evaluation as a pharmacological tool in animal models of disease. C16 showed suboptimal pharmacokinetics with limited or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Moreover, the anticancer effect of chalcones in experimental animals has also been shown [ 27 , 28 ]. Additionally, in contrast to “classical” anticancer agents, chalcones are well tolerated as documented in animal as well as clinical studies [ 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the anticancer effect of chalcones in experimental animals has also been shown [ 27 , 28 ]. Additionally, in contrast to “classical” anticancer agents, chalcones are well tolerated as documented in animal as well as clinical studies [ 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that oral administration of chalcones is well‐tolerated and do not cause toxicity at doses up to 300 mg/kg 22–25 . However, as this is the first study to evaluate the effects of systemic administration of Chalcone T4, we performed the in vivo toxicity experiment using mice prior to subsequent studies using rats because of the reduced body weight and consequently reduced amount of Chalcone T4 needed.…”
Section: Methodsmentioning
confidence: 99%
“…Environment of rats was maintained with temperature ranged 25 ± 5˚C and 12 hours day night cycle. Free excess to clean drinking water and standard rodent diet adlibitum were provided during the whole study period 9 . They were allocated randomly in two (02) groups with eight (08) rats in each group.…”
Section: Methodsmentioning
confidence: 99%